2022
DOI: 10.1177/14613484221122732
|View full text |Cite
|
Sign up to set email alerts
|

Identifying dominant components of vibrational energy flow in U-rib plates of bridge based on structural intensity

Abstract: Stiffened U-rib plates are the elementary components of steel box girders in bridges that directly bear the input external energy before transferring it to other components. Research on the dynamic characteristics of stiffened U-rib plates is the basis for examining vibration and noise in steel box girders. Most relevant studies have focused on the vibrational modes and single-frequency responses in this context, and few researchers have sought to optimize the design of stiffened U-rib plates to reduce respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The results showed that the electromagnetic field could change the damping energy dissipation, and the loss factor increased with the increase of magnetic field intensity within a certain range of acceleration, and decreased with the increase of magnetic field intensity beyond the acceleration threshold. Kong Derui et al [43] took the steel box girder as the prototype to make the scaled specimen of U-rib-stiffened plate with embedded particle damping. The results show that particle damping has good vibration and noise reduction effect in a wide band, and the loss factor can be increased to 2~2.5 times of the original structure.…”
Section: Experimental Study On Particle Dampingmentioning
confidence: 99%
“…The results showed that the electromagnetic field could change the damping energy dissipation, and the loss factor increased with the increase of magnetic field intensity within a certain range of acceleration, and decreased with the increase of magnetic field intensity beyond the acceleration threshold. Kong Derui et al [43] took the steel box girder as the prototype to make the scaled specimen of U-rib-stiffened plate with embedded particle damping. The results show that particle damping has good vibration and noise reduction effect in a wide band, and the loss factor can be increased to 2~2.5 times of the original structure.…”
Section: Experimental Study On Particle Dampingmentioning
confidence: 99%